Atrophy of anterior digastric muscle detected during ultrasound of the neck - a prospective clinical study. Issue 3 (April 2016) - Gibson, Daren; Dwivedi, Raghav C.; Bowles, Christopher; Brennan, Peter A.
Abstract: Anatomical variants that affect both the anterior and posterior digastric muscles are well described, and include duplications and variable origin or sites of insertion. Although agenesis or atrophy of the anterior digastric occurs in up to 40% of patients with hemifacial microsomia, to our knowledge, it has been reported only rarely in those without this syndrome. To minimise observer bias and to establish the incidence of anomalies and atrophy of this muscle, a prospective 6-year study was conducted by an experienced consultant radiologist in all patients referred for ultrasound of the head and neck. Unilateral atrophy or absence of the anterior digastric muscle was seen in 3 of 1484 patients (0.2%). All 3 were female, and they had no symptoms or clinical signs related to the finding. One subsequently had a magnetic resonance scan. Non-syndromic absence or atrophy of the anterior digastric muscle is rare, and seems to be a unilateral phenomenon. Recognition of this variant could be important before operations in which it may be used as a landmark, or during procedures in which it is used, for example, for reanimation of a static lip or during reconstruction with a submental island flap.